Effects of Outcomes and Random Arbitration on Emotions in a Competitive Gambling Task - Bediou, Benoit; Mohri, Christelle; Lack, Jeremy; Sander, David (Frontiers in Psychology, 2011)
Research on self-serving biases in judgments and decision-making suggests that individuals first evaluate the outcomes they get, and then the procedures by which these outcomes were obtained. Evidence also suggests that the appraisal of the former (outcome favorability) can bias the appraisal of the latter (procedural fairness). We investigated the nature of the emotions that are elicited by these appraisals by using a new paradigm in which participants performed a choice task between pairs of competing gambles against a virtual opponent. Conflicts (when the participant selected the same gamble as his virtual opponent) were resolved by a neutral arbitrator who either confirmed the participant’s choice (“pro-self”) or attributed his gamble to the virtual opponent (“pro-competitor”). Trials in which the participant and his virtual opponent selected different gambles (“no-conflict”) served as a control condition. In order to validate this new task, emotional reactions to the outcomes of the gambles were measured using self-reports, skin conductance responses, and facial electromyography (zygomaticus, corrugator, and frontalis). In no-conflict trials, effects of counterfactual thinking and social comparison resulted in (i) increased happiness as well as SCR and zygomaticus activity for wins compared to losses (valence effect) and for high compared to low gains (magnitude effect), and (ii) increased anger, regret, disappointment, and envy for losses compared to wins (valence effect). More importantly, compared to no-conflict trials and to pro-self awards with similar outcomes, pro-competitor awards increased subjective reports of anger for unfavorable outcomes, and increased happiness and guilt for favorable outcomes. Although the outcomes were independent from the arbitrators’ decisions, and both the arbitrators’ decisions and the outcomes were kept equally likely, individuals tended to attribute their outcomes to unfair arbitrators, reacting emotionally, especially when the modification of their initial choice for a gamble led to a negative outcome.